Violência e intolerância sob o governo de Constâncio II : as implicações sociopolíticas do arianismo - Entringer, Giovanna (2009)
The aim of this dissertation is to discuss the political and social impact of Arianism under the government of Constâncius II (337-362 BC). The Arianism emerged from the preaching of the Egyptian presbyter Arius, which questioned the divinity of Christ. His ideas spread through Empire even when they have been condemned by the bishop of Alexandria, Alexandre. These ideas divided the Christians’ view and began a controversy ever seen before. For decades, the Arianism mobilized many strata of Roman society including clergy, laity and emperors. The absence of a doctrine that could be accepted by all bring about many councils that failed to solve the quarrel. The emperors, especially Constancius II, started a policy of interference in the church. Constantius initiates a policy of exile and imprisonment against those who were considered a menace to the order and unity of the Church. But this direct action on Christian communities produced many reactions. The reaction of Athanasius was quite intense which is why the bishop was exiled twice by Constantius. Known as the main opponent to the Arians, Athanasius left us a set of documents that help us to investigate his position towards the imperial power and we also will be able to learn about the importance of Arian controversy in the period. The mobilization of the population of the Empire, particularly in the East, because of the Arian controversy helps us to understand the scenario of religious intolerance at that time and in the city of Alexandria where we see the emergence of numerous conflicts in which Arians and Nicene were on opposing sides.